The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1002/chin.199037215
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, Structure and Cytostatic Activity of a Series of 2‐Substituted Perimidines.

Abstract: 215ChemInform Abstract The presence of a basic nitrogen in the side chain of the title compounds, e.g. (IV) and (VI), is important for their in vitro cytotoxic activity. The most active derivative is (IVa).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Perimidine derivatives, which are key nitrogen-containing heterocycles, have a variety of biological and pharmacological actions, including antibacterial, antimicrobial, anticancer, and anti-inammatory characteristics. [97][98][99] Their high electron-donating properties make them useful intermediates in the synthesis of symmetrical squarylium dyes for NIR absorption. In addition, they serve as antioxidant stabilizers, photochromic chemicals, catalysts, ligand scaffolds, and supramolecular stoppers.…”
Section: Squaric Acid Catalyzed Reactionsmentioning
confidence: 99%
“…Perimidine derivatives, which are key nitrogen-containing heterocycles, have a variety of biological and pharmacological actions, including antibacterial, antimicrobial, anticancer, and anti-inammatory characteristics. [97][98][99] Their high electron-donating properties make them useful intermediates in the synthesis of symmetrical squarylium dyes for NIR absorption. In addition, they serve as antioxidant stabilizers, photochromic chemicals, catalysts, ligand scaffolds, and supramolecular stoppers.…”
Section: Squaric Acid Catalyzed Reactionsmentioning
confidence: 99%
“…Those authors revealed the fused tricycle perimidine was the minimal structure condition for the intercalative biding with DNA and affected by the variation in side chain of chromophore. Braña et al demonstrated that the 2-subtitutes perimidines-induced cytotoxicity action through the presence of basic nitrogen bearing to methyl groups [12]. As new chemicals synthetized, it is worthwhile to be submitted to toxicity studies in order to optimize later the therapeutic doses for heal human diseases.…”
Section: Perimidin-2-yl)-6-mentioning
confidence: 99%
“…Brafial et al [124] described the synthesis, cytotoxic activity, and structure-activity relationship (SAR) of 2-substituted perimidines. Perimidines were synthesized from the reaction of NDA with different compounds like p-toluenesulphonate and cyanamide and substituted amines.…”
Section: Biologic Applicationsmentioning
confidence: 99%
“…It is used as a coloring agent and dye intermediate in fibers and plastic synthesis, carbene ligand generation, and corrosion inhibitors [10][11][12]. It also works as a potent drug against various diseases and behaves as antitumor, antimicrobial, antifungal, antiulcer, antioxidant, anti-inflammatory agent, and corticotropin-releasing factor (CRF) receptor-selective antagonists [13][14][15][16] etc. (Scheme 2).…”
mentioning
confidence: 99%